Abandono parental y su influencia en la conducta agresiva de un niño - Tapia Alvarado, Karen Janneth (2020)
The importance of this study lies in the collection of the necessary information for the assertion of the subject, its usefulness for studies that are related to this research, it is also required to generate a great impact in the different social areas to which it belongs and especially to the Technical University of Babahoyo. The purpose of this case study is to determine how parental abandonment influences aggressive behavior in a child of the San José Educational Unit, in which a case study was carried out using the psychodiagnostic tools and techniques necessary to know the situation Current student among which are the clinical interview, clinical history and application of psychometric tests. Aggressiveness in childhood could cause problems in the future, and could greatly affect the school area, lack of capacity for socialization and adaptation to society. These teenage behaviors can associate the search to consolidate their identity and autonomy, or the result of the previous process focused on family relationships and the interaction of forces with the school.